Natural killer T cell ligand alpha-galactosylceramide protects against gut ischemia reperfusion-induced organ injury in mice. (November 2018) - Zhang, Jia; Bi, Jianbin; Ren, Yifan; Du, Zhaoqing; Li, Teng; Li, Qingshan; Ke, Mengyun; Dong, Jian; Lv, Yi; Wu, Rongqian
Highlights: The immune response plays an important role in I/R-induced organ injury. α-GalCer is a potent natural killer T (NKT) cell stimulator. α-GalCer significantly reduced gut and lung injury after gut I/R. α-GalCer markedly stimulated the produce of IL-4, IL-10 and IFN-γ in gut I/R mice. The beneficial effects of α-GalCer in gut I/R were NKT cell dependent and mediated through upregulation of IL-4 and IL-10. Abstract: Background & Aims: Gut ischemia reperfusion (I/R) injury is a life-threatening condition. The immune response plays an important role in I/R-induced organ injury. Alpha-galactosylceramide (α-GalCer) is a potent natural killer T (NKT) cell stimulator. Activation of NKT cells by α-GalCer has been shown to reduce I/R-induced injury in the liver and heart. However, whether α-GalCer has any protective effects on gut I/R-induced organ injury remained unknown. The aim of this study was to test the hypothesis that α-GalCer attenuates gut I/R-induced local and remote organ injury through modulating immune responses. Methods: Gut ischemia was induced by placing a microvascular clip across the superior mesenteric artery for 30 min in male adult mice. After removing the clip, α-GalCer (2 µg/mouse) or normal saline containing 0.5% Tween 20 (Vehicle) was administered intraperitoneally. Blood, gut, lung and mesenteric lymph node (MLN) samples were collected 4 h after reperfusion to detect bacterial translocation, tight junction protein, tissue damage, edema, apoptosis, IL-4, IL-10, IFN-γ and TNF-α levels. Results: α-GalCer significantly reduced bacterial translocation to the MLN, restored tight junction protein and attenuated gut and lung injury after gut I/R. α-GalCer markedly stimulated the production of IL-4, IL-10 and IFN-γ, but had no obvious effects on TNF-α production in gut I/R mice. Pretreatment with anti-CD1d, IL-4 or IL-10, but not IFN-γ blocking antibodies abolished the protective effects of α-GalCer in gut I/R. Conclusions: α-GalCer treatment improved gut barrier function and attenuated gut and lung injury after gut I/R. The beneficial effects of α-GalCer in gut I/R were NKT cell dependent and mediated through upregulation of IL-4 and IL-10. Thus, activation of NKT cells by α-GalCer may serve as a novel option in the treatment of gut I/R injury.